Asociación de los estilos de personalidad con los niveles de ansiedad y de depresión en ingresantes a estudios generales de medicina - Valderrama Aguilar, Johan Paúl (2019)
OBJECTIVE: To determine the association between personality styles and levels of anxiety and of depression in general studies of medicine of the UNT. MATERIAL AND METHOD: Correlational and transversal observational study. The three test (MIPS, BAI, BDI) were developed to 99 students of the first year of medicine, who apply the inclusion and exclusion criteria. Subsequently, the gamma test was applied to the obtained data to identify the associations. RESULTS: Styles with positive association (maladaptive) for anxiety and depression were the same in: Accommodation, Hesitation, Preservation, Retraction, Innovation and Discrepancy; the exclusives were Intuition for Anxiety, Subjection and Concordance for depression. While the styles that are negatively associated (adaptive) with depression included those of anxiety: Systematization, Firmness, Opening, Control and Modification; and the exclusive ones of depression: Extraversion, Conformism and Sensation. CONCLUSION: There is association between some personality styles and the presence of anxiety and depression. Students with marked traits in "maladaptive" styles and absence of "adaptive" styles are more likely to suffer from anxiety and / or depression.